Science-literacy-Based Teaching Materials Training Management Model: Improving the Professional Competence of Middle School Teachers - Rini Ismeini; Arif Rahman; Yuniarto Mudjisusatyo (RIRAI Publisher, 2024)
This research aims to (1) determine the effectiveness of the Scientific Literacy-Based Teaching Materials Training Management Model based on material experts, learning design experts, and teacher responses. (2) determine the effectiveness of the scientific literacy-based teaching materials training management model. This research was conducted at SMP N 11 Medan in June–October 2023, using descriptive data analysis techniques. The development of the training model was carried out using the Thiagarajan Four-D (4-D) development model, which consists of four stages, namely definition, design, development, and dissemination. The resulting product is a training model that will be used by teachers at SMP N 11 Medan. The feasibility of the model was assessed by validation experts. The results of the material expert assessment show that it is in the very good category, with an average percentage of 90.05% (very good), design experts at 90.50% (very good), and teacher respondents at 91.6% (very good). Test the effectiveness of the model with the results of the known value tcount = 3.263 while ttable = 2.042, which means that there is an influence of using a model based on scientific literacy in the ecosystem in increasing students' grades in class, so it can be concluded that the research product for the development of scientific literacy-based teaching material training management is a training model that is suitable for use as a training model for teachers.